Systematic Review and Pharmacological Considerations for Chloroquine and Its Analogs in the Treatment for COVID-19 - Peng, Hongwei; Chen, Zhangren; Wang, Yunyun; Ren, Simei; Xu, Tiantian; Lai, Xin; Wen, Jinhua; Zhao, Mengjun; Zeng, Chuanfei; Du, Lijuan; Zhang, Yanmei; Cao, Li; et al. (Frontiers in Pharmacology, 2020)
COVID-19 has been announced pandemic by WHO and over 17,000,000 people infected (Till April 21st 2020). The disease is currently under control in China, with a curative rate of 86.8%. Chloroquine (CQ) is an old anti-malarial drug with good tolerability, which had proved to be effective in previous SARS-coronavirus, which spread and disappeared between 2002-2003. In vitro studies demonstrated the efficacy of CQ in curing COVID-19. Consequently, via analytical PBPK modeling, a further preliminary clinical trial has proved the efficacy and safety of CQ in China., and multiple clinical trials were registered and approved to investigate the activity of other analogs of CQ against COVID-19. We have listed all the clinical trials and made a meta-analysis of published data of hydroxychloroquine (HCQ). HCQ could increase the CT improvement and adverse reactions (ADRs) significantly though there was considerable heterogeneity among current researches. Actually, CQ and its analogs have unique pharmacokinetic characteristics, which would induce severe side effects in some circumstances. We have then summarized pharmacological considerations for these drugs so as to provide to the busy clinicians to avoid potential side effects when administered CQ or its analogs to COVID-19 patients, especially in the elderly, pediatrics, and pregnancies.